Ecology of Dangs Forests (Gujarat)-I Phytosociology of the Forests in Ahwa ’block’ - Kuruvilla, K. (Indian Forester, 1967)
The series of present papers deal with the ecology of Dangs Forests (Gujarat State). The study which is first of its type in this State includes the pattern of distribution of various forest communities in relation to factors of topography, soil, microclimate and biota and to assess their ecological status. The situation and topography have been described in the present paper of the series. Underlying rocks are basalt (Deccan trap) which on weathering give rise to three types of soils depending upon the drainage pattern. Climate of Dangs is salubrious with an average annual rainfall of 1,729 mm. The mean maximum temperature is 41.2Â°C and mean minimum is 14Â°C. In general the dominant crop of the fortest is class IV (of al1- India Teak). For the sake of convenience the entire Danga forest has been arbitrarily divided into twenty blocks and the present paper describes the ecology of the forest in Ahwa block, which consists of six forest-localities (stands), namely Ghogli, Nilsaka, Borkhet, Karanjwa, Wadthal and Borkhal.The phytosociological characters of the six stands have been discussed under:- i) Differences within the stands with regard to topogyaphy (ii) Intercomparisons between stands Soil profiles have been studied and various characters are correlated with different physiographical situations and vegetation in different stands.